Skeletal ligament healing using the recombinant human amelogenin protein - Hanhan, Salem (J Cell Mol Med, 2016)
Injuries to ligaments are common, painful and debilitating, causing joint instability and impaired protective proprioception sensation around the joint. Healing of torn ligaments usually fails to take place, and surgical replacement or reconstruction is required. Previously, we showed that in vivo application of the recombinant human amelogenin protein (rHAM (+)) resulted in enhanced healing of the tooth‐supporting tissues. The aim of this study was to evaluate whether amelogenin might also enhance repair of skeletal ligaments. The rat knee medial collateral ligament (MCL) was chosen to prove the concept. Full thickness tear was created and various concentrations of rHAM (+), dissolved in propylene glycol alginate (PGA) carrier, were applied to the transected MCL. 12 weeks after transection, the mechanical properties, structure and composition of transected ligaments treated with 0.5 μg/μl rHAM (+) were similar to the normal un‐transected ligaments, and were much stronger, stiffer and organized than control ligaments, treated with PGA only. Furthermore, the proprioceptive free nerve endings, in the 0.5 μg/μl rHAM (+) treated group, were parallel to the collagen fibres similar to their arrangement in normal ligament, while in the control ligaments the free nerve endings were entrapped in the scar tissue at different directions, not parallel to the axis of the force. Four days after transection, treatment with 0.5 μg/μl rHAM (+) increased the amount of cells expressing mesenchymal stem cell markers at the injured site. In conclusion application of rHAM (+) dose dependently induced mechanical, structural and sensory healing of torn skeletal ligament. Initially the process involved recruitment and proliferation of cells expressing mesenchymal stem cell markers.